Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.4 - Complex Numbers - Problem Set 11.4: 45

Answer

$-21-12i$

Work Step by Step

We multiply each term of the first complex number with the second complex number and then simplify: $(-2-3i)(6-3i)$ =$-2(6-3i)-3i(6-3i)$ =$-12+6i-18i+9i^{2}$ =$-12-12i+9(-1)$ [We substitute -1 in place of $i^{2}$ as $i^{2}=-1$] =$-12-9-12i$ =$-21-12i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.